(untitled) (Gestão & Regionalidade, 2025)
The study of institutional change is an area of â€‹â€‹research in organizational theory, and the study of regional politics is on the institutional research agenda. This implies exploring how institutions matter for regional development and how the role of the State impacts on the environment of regions formed by micro and small businesses. Thus, this article presents and analyzes the type of institutional change in the productive agglomeration of footwear in Jaú/SP. This is a case study of a descriptive, exploratory and historical nature. The mixed approach subsidized the methodology, with quantitative analysis for economic data and qualitative analysis for data collected through documents and an interview script with nine actors linked to the governance of the cluster. The results pointed to the layered type of change, when small modifications are introduced and coexist with old practices. The events altered the socioeconomic conditions, but did not modify the institutional structure.